Isolation and Characterization of Lactic Acid Bacteria From Sago Wastewater As Antibacterial - Satwika Tri Rahmadana; Eka Astuty; Ony Wibriyono Angkejaya (Universitas Wijaya Kusuma Surabaya, 2024)
Background: Foodborne diseases are infections of the gastrointestinal tract caused by food containing microbiological agents and usually, these infections affect groups of individuals who have low immune systems. Lactic acid bacteria (LAB)are bacillus-shaped Gram-positive bacteria that work by inhibiting pathogenic bacteria that cause foodborne diseases. Maluku is a region in Indonesia rich in sago production. Sago ihur (Metroxylon sylvestre) and tuni (Metroxylon rumphii) are types of sago commonly found in Maluku. Sago is rich in carbohydrates and therefore has the opportunity to produce LAB. This study aimed to isolate and characterize LAB from sago wastewater was a laboratory experimental research with descriptive method using primary data. Methods: Bacterial isolation was carried out using a selective media. Characterization carried out by macroscopicly characterization by observing shape, margin, elevation, pigmentation, appearance, optical properties, and texture. Microscopic characterization was performed using Gram and spore staining. Results: The results of this study showed that five bacterial isolates (I1, I2, T3, T4, and I5) were successfully isolated in a round shape, flat edges, yellowish white color (not pigmented), shiny appearance, and mucoid texture, but isolate T3 showed a raised elevation and translucent to light (transparent), while for other isolates it was convex and translucent, and non-spore forming gram positive. Conclusion: Antibacterial tests against S. aureus and E. coli showed no inhibition zones. LAB isolates from sago wastewater showed no significant antibacterial effect